Implementasi Zakat Penghasilan sebagai Pengurang Pajak (Penguatan Literasi Fiskal dan Tata Kelola Lembaga Zakat di Kota Samarinda) - Mubarak, Ahmad Habibie; Salamah, Ummu (Abdimas Mandalika, 2026)
Abstract: The implementation of income-based zakat as a deductible component of taxable income integrates both religious and national fiscal obligations. This policy has a strong legal foundation through laws governing zakat management and income tax. However, in practice, the utilization of zakat as a tax deduction remains suboptimal and ineffective. This article aims to analyze the implementation of the income zakat policy as a tax deduction in Samarinda City, with a focus on public fiscal literacy and the governance of zakat institutions. The study employs a socio-legal approach through community service activities, including socialization programs, focus group discussions, and administrative assistance involving BAZNAS, Islamic charitable institutions (LAZ), Zakat Collection Units (UPZ), the Tax Service Office, and Muslim workers. The findings indicate that the main obstacles to implementation lie in the low level of taxpayers’ understanding of the administrative mechanisms of zakat as a taxable income deduction, limited integrated socialization, and the absence of an integrated zakat and tax information system. Nevertheless, zakat institutions in Samarinda have demonstrated efforts toward professionalization through improved record-keeping systems and the digitalization of services. Strengthening fiscal literacy, enhancing inter-institutional coordination, and developing integrated data systems are key to optimizing the role of zakat as an instrument of social justice and a support for national fiscal policy.Abstrak: Implementasi zakat penghasilan sebagai pengurang PKP mengintegrasikan kewajiban keagamaan dan fiskal nasional. Kebijakan ini memiliki landasan hukum kuat melalui undang undang pengelolaan zakat dan pajak penghasilan. Namun dalam praktik pemanfaatan zakat sebagai pengurang pajak masih belum optimal dan efektif. Artikel ini bertujuan menganalisis implementasi kebijakan zakat penghasilan sebagai pengurang pajak di Kota Samarinda dengan menitikberatkan pada aspek literasi fiskal masyarakat dan tata kelola lembaga zakat. Penelitian ini menggunakan pendekatan yuridis-sosiologis melalui kegiatan pengabdian kepada masyarakat yang meliputi program sosialisasi, diskusi kelompok terarah, serta pendampingan administratif dengan melibatkan BAZNAS, Lembaga Amil Zakat (LAZ), Unit Pengumpul Zakat (UPZ), Kantor Pelayanan Pajak, serta pekerja Muslim. Hasil penelitian menunjukkan bahwa kendala utama implementasi terletak pada rendahnya tingkat pemahaman wajib pajak terhadap mekanisme administratif zakat sebagai pengurang PKP, terbatasnya sosialisasi yang terintegrasi, serta belum tersedianya sistem informasi zakat dan pajak yang terintegrasi. Meskipun demikian, lembaga zakat di Kota Samarinda telah menunjukkan upaya profesionalisasi melalui perbaikan sistem pencatatan dan digitalisasi layanan. Penguatan literasi fiskal, peningkatan koordinasi antarlembaga, serta pengembangan sistem integrasi data menjadi kunci untuk mengoptimalkan peran zakat sebagai instrumen keadilan sosial dan pendukung kebijakan fiskal nasional.